2019
DOI: 10.1016/j.celrep.2019.04.072
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A from Granuloma Macrophages Regulates Granulomatous Inflammation by a Non-angiogenic Pathway during Mycobacterial Infection

Abstract: Highlights d Mycobacterial granulomas contain a subpopulation of VEGF-A-producing macrophages d VEGF-A recruits macrophages to the granuloma via a nonangiogenic pathway d VEGF-A inhibition reduces granulomatous inflammation with limited effect on protection d Mice with myeloid-specific deletion of VEGF-A are more resistant to Mtb infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 74 publications
(84 reference statements)
2
45
1
Order By: Relevance
“…In our model of dermal Leishmania infection, macrophages were the major VEGF-Aexpressing cell type in vivo. These results are consistent with granuloma macrophages being the major producers of VEGF-A during mycobacterial infection (42). We did not find elevated VEGF-A expression in the CD45 Ϫ cell fraction (which would contain fibroblasts), suggesting that fibroblasts and epidermal cells are not the dominant VEGF-A-producing cell type during infection, despite the ongoing wound healing response following L. major infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our model of dermal Leishmania infection, macrophages were the major VEGF-Aexpressing cell type in vivo. These results are consistent with granuloma macrophages being the major producers of VEGF-A during mycobacterial infection (42). We did not find elevated VEGF-A expression in the CD45 Ϫ cell fraction (which would contain fibroblasts), suggesting that fibroblasts and epidermal cells are not the dominant VEGF-A-producing cell type during infection, despite the ongoing wound healing response following L. major infection.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to Bartonella, the bacterium Clostridium difficile induces HIF-dependent VEGF-A production and vascular permeability to promote disease pathogenesis (53). Mycobacterium tuberculosis infection also induces VEGF-A production by macrophages, and the serum level of VEGF-A is elevated in tuberculosis patients (42,54). Importantly, VEGF-A production during Mycobacterium marinum infection in zebrafish promotes bacterial growth and dissemination (55).…”
Section: Discussionmentioning
confidence: 99%
“…(Osherov and Ben-Ami 2016; Polena et al 2016; Oehlers et al 2015; Datta et al 2015) Mycobacterium-mediated angiogenic processes and granuloma vascularization result from the secretion of proangiogenic factors by the infected immune cells that compose the granuloma and play a complex and evolving role during the course of infection. (Torraca et al 2017; Polena et al 2016; Oehlers et al 2015; 2017) Extensive work has been conducted on understanding the role of angiogenesis in granuloma outcome, finding that inhibition of VEGF and other signaling pathways reduces pathogenicity and dissemination of infectious mycobacteria(Polena et al 2016; Oehlers et al 2015; Harding et al 2019) while normalizing surrounding vasculature, improving small molecule delivery, and decreasing hypoxia within the granuloma. (Datta et al 2015) Similarly, we observed increased secretion of VEGF from infected cells within our microscale granuloma model (Figure 3C), and therefore sought to illustrate one potential use of our platform as a complimentary tool for studies examining this infection-mediated process.…”
Section: Resultsmentioning
confidence: 99%
“…Myeloid-derived VEGF-A was shown to regulate angiogenesis in mouse models of lung injury 59 and melanoma 20 . Alternatively, myeloid-derived VEGF-A was shown to control in ammation independently of vasculogenic effects in granulomatous in ammation 60 and in myocardial infarction 42 . A key question raised by our study is whether IL-1β and VEGF-A contributed to tumor progression in a sequential and stage-speci c manner, or in a synergic way.…”
Section: Discussionmentioning
confidence: 99%